CHANGES IN POLICY DIRECTION AND LEGAL CONSEQUENCES LAW NO. 17 OF 2023 CONCERNING HEALTH ON ABORTION ISSUES IN THE TRANSITION PERIOD FOR RENEWING THE CRIMINAL CODE - Novi Enjelina Putri; Abdul Madjid; Bambang Sugiri (CV. RADJA PUBLIKA, 2024)
This research began with confusion regarding changes in the direction of legal regulatory policies regarding abortion in Indonesia. This is proven by the amendment to the Health Law Number 17 of 2023 which is part of the health omnibus law, which can result in multiple interpretations because it refers to the criteria specified in the criminal code. However, it is not explained which criminal law book will be used, which could create gaps in the application of criminal law in cases of legal abortion in Indonesia. The possibility of interpretation in determining the criminal law book is due to the transition period for the implementation of the new criminal law book, namely Law Number 1 of 2023, which will still come into force in 2026. The difference in the policy direction of the old criminal law book and The new one is very significant because the new one regulates the exceptions to which abortion can be carried out, whereas the old one does not see any reason and categorizes abortion as a criminal offense and will be subject to imprisonment for those who violate it. These differences in provisions will certainly have quite different legal consequences if the legal regulations are incorrectly applied in dealing with the issue of legal abortion in Indonesia. If they are incorrect then the disadvantage is the pregnant mother who has the right to abortion. This research uses normative legal research by looking at conceptual approaches and also legislation. With the aim of seeing how the legislation regarding abortion continues to undergo changes and the legal consequences that arise from these policies.